Controlling protein activity by dynamic recruitment on a supramolecular polymer platform - Sjors P. W. Wijnands (Nature Portfolio, 2018)
DNA-origami allows the precise recruitment of DNA-protein conjugates but lacks the dynamics found in natural protein assemblies. Here the authors present a synthetic polymer platform that combines the dynamics of supramolecular polymers with the programmability of DNA-mediated protein recruitment.